Perkembangan Teknologi Tungku Lebur Logam Besi pada Zaman Kuno di Indonesia - Harry Octavianus Sofian (Pusat Penelitian Arkeologi Nasional, 2021)
Abstract. Technological knowledge of the use of metals is inseparable from human knowledge in the processing pyrotechnics of fire as a power in high temperature processes for producing objects. The fire is used for smelting and casting in melting furnaces. Metal smelting furnace is a heat production device, which is used to purify the metal, in this case iron. This paper aims to determine the development of ferrous metal smelting furnace technology in Indonesia with the library research method from the results of previous studies. Based on the results of the analysis, there are four technologies for smelting iron, namely pit kiln, bloomery furnace, blast furnace, and induction furnace. Of the four technologies, three are in use in Indonesia, namely bloomery furnace, blast furnace, and induction furnace.